Roles of glycans in yeast cell walls - Lipke, Peter (Henry Stewart Talks, 2012)
The overall architecture of yeast cell walls and the roles of glycans, Structure and biosynthesis of major cell wall components, A scheme for cell wall assembly and crosslinking, Cell wall dynamics in growth, budding, stress response, cell adhesion, and mating, Cell wall structure in other fungi and a relationship among eukaryotic extracellular matrices
Archived at 2022/11/30